Characterization of visual cognition in pre-manifest, manifest and reduced penetrance Huntington’s disease - Rocio Del Pino; Maria Ángeles Acera; Amaia Ortiz de Echevarrría; Beatriz Tijero; Marta Ruiz-Lopez; Johanne Somme; Javier Ruiz-Martínez; Andrea Gabilondo; Ioana M. Croitoru; Lara Pardina; Naia Ayo-Mentxakatorre; Ane Murueta-Goyena; et al. (Scientific Reports)
Abstract Cognitive and visual impairment are common in Huntington’s Disease (HD) and may precede motor diagnosis. We investigate the early presence of visual cognitive deficits in 181 participants, including HD carriers (40 pre-manifest, 30 early manifest, 27 manifest, and 6 reduced penetrance) and 78 healthy controls (HC). Significant differences in visual memory were observed between reduced penetrance and pre-manifest groups (p = .003), with pre-manifest showing worse performance. Age, education, CAG repeats, motor status, executive function, and verbal fluency, accounted for up to 72.8% of the variance in general and visual cognitive functions, with motor status having the strongest impact on visual domains in HD carriers. In pre-manifest HD, visual cognitive domains were primarily influenced by executive function, verbal fluency, age, and CAG repeats, while in early and manifest stages motor status and verbal fluency becomes more influential. ROC analyses showed that especially visuospatial abilities, visual memory, and visual attention (AUC = 0.927, 0.878, 0.874, respectively) effectively differentiated HC and pre-manifest from early and manifest HD. Early assessment of visual cognitive domains, particularly visual memory, could be an early marker of cognitive decline in HD. Our findings highlight the different profiles of impairment in visual cognition across HD carriers.